Islam dan Demokrasi Pasca Orde Baru - Widodo, Sembodo Ardi (Unisia, 2012)
This article explains the relation and contribution of state, civil society and Islam in the process of changing leadership and developing society in order to create the process of democracy in the post-failing New Order. In a historical context, the civil society and Islam, representing the majority of Indonesian people, plays an important role in determining the reformation of the social and political fields, and are directly involved in the process of changing and creating the process of democracy, compatible with the condition of political development in Indonesia. Although these three of state, civil society and religion (Islam) have some weakness, but in a historical context of Indonesia, they have become the success key in creating the process of democracy and changing leadership in the postfailing New Order. Keywords: Islam, relation, contribution, democracy